GANDHIAN NON-VIOLENT DEMOCRACY- AN ALTERNATIVE MODEL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The problem of violence is one of the many challenges that democracy faces today, but paradoxically enough, democratic form of government was established with the promise of a peaceful society. In reality it has largely failed to achieve its intended goal. Why? because it could not grow into what it was expected to be: a government of the people, by the people, for the people to use Abraham lincon’ definition. And it is this failure of democracy to be the authentic voice of all people that seems to be responsible for the eruption of violence that goes against the very sprite of democracy. In all existing democracies, the opinion of an individual or of a section of the people often lie neglected, even if it is sound, as the democracies are guided by the views either of popular majority or of the dominating elitist minority. Moreover, while in capitalist or liberal democracy, political liberty rather than economic equality is emphasized, in socialist or Marxist democracy political liberty is sacrificed at the altar of economic equality. All these factors tend to generate discontent among those who stand marginalized in democracy, a discontent that may create a climate of tension and strife, sow the seeds of violence in society, but how to create a society that is free from these ills? The democracy of the world may turn to Gandhi for an answer, to transform democracy into a non violence pacific social rather than political order Gandhi offers two important suggestions. First, democracy must begin to work the lowest level, that is from the level of ‘Gram- Panchayet’, this will stave off people ‘s discontent by giving them a sense of participation in the democratic system. Second, he prescribes some moral principles to be cultivated, like truthfulness, ahimsa, toleration, self – sacrifice and self – suffering. Those   measures, if taken will liberate Indian democracy form limitation of its western counterpart and halp the evolution of a democracy that is true to Indian genius.